ПОРІВНЯННЯ СТРУКТУРНОЇ ОРГАНІЗАЦІЇ УГРУПОВАНЬ ФІТОПЛАНКТОНУ УКРАЇНСЬКОГО ШЕЛЬФУ Й ВІДКРИТИХ ВОД ЧОРНОГО МОРЯ НАВЕСНІ 2016 РОКУ - Зотов, А.Б.; Грандова, М.О.; Зотова, О.В.; Теренько, Г.В. (Marine Ecological Journal, 2023)
The results of researches of phytoplankton that was held in May-June 2016 within the framework of the EMBLAS project are presented. The results of the two cruis made it possible to compare the structure and distribution of phytoplankton in the shelf (NPMS-UA (Shelf-UA)) and open waters (JOSS-UA (OW-UA)) of Ukraine. The highest species diversity was found in the stations of Shelf-UA (224 species). In the open waters of the number of identified species decreases (138 species). Dinophyceae contribution in species diversity on the shelf was lower, and Bacillariophyceae contribution was higher than in open waters. The average biomass on the shelf (418.10 mg/m3) exceeded the similar value of open waters (274.23 mg/m3). Analysis of the vertical distribution showed the maximum values of abundance and biomass in the upper layer (to 20 m). The general trend of the spatial distribution of phytoplankton biomass was a decrease of the average values from the Ukrainian shelf to the open waters. High contribution of Bacillariophyceae in the average abundance at Shelf-UA stations (85%) decreased to 50% in OW-UA. The relative contribution of Prymnesiophyceae in the total abundance contrary increased from 4% (Shelf-UA) to 44% (OW-UA). Of the 10 mass species registered in the studied area, only Pseudo-nitzschia delicatissima reached the level of bloom (to 3.39∙106 cells/L for Shelf-UA and 2.39∙106 cells/L for OW-UA). In the study area was identified 14 potentially toxic species. The highest average abundance (302.46∙103 cells/L) and biomass (143.09 mg/m3) was formed by Pseudo-nitzschia delicatissima. Among the investigated sites, the most favorable environmental conditions were observed in the open Ukrainian shelf water (OW-UA). Worst category of ESC was noted in the Shelf-UA in the Danube Region (Poor).